THE MULTI-ACTIVITY HERBACEOUS VINE - TINOSPORA CORDIFOLIA - KATTUPALLI, SOWJANYA; VESTA, VAISHNAVI; VANGARA, SANDHYA; SPANDANA, UPPULURI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Tinospora cordifolia (Willd.) Miers ex Hook. F. and Thoms is a large deciduous, climbing shrub found throughout India, especially in the tropical parts ascending to an altitude of 300 m and also in certain parts of China (Anonymous). It belongs to the family Menispermaceae. It is known as heart-leaved Moonseed plant in English, Guduchi in Sanskrit, and Giloy in Hindi. It is known for its immense application in the treatment of various diseases in the traditional ayurvedic literature. T. cordifolia, also named as “heavenly elixir,” is used in various ayurvedic decoctions as panacea to treat several body ailments. (Mishra R,) Its root stems, and leaves are used in Ayurvedic medicine. T. cordifolia is used for diabetes, high cholesterol, allergic rhinitis (hay fever), upset stomach, gout, lymphoma and other cancers, rheumatoid arthritis, hepatitis, peptic ulcer disease, fever, gonorrhea, syphilis, and to boost the immune system (WebMD).